Cooling power and characteristic times of composite heatsinks and insulants. (February 2018) - Shamberger, Patrick J.; Fisher, Timothy S.
Graphical abstract: Highlights: Develop technique to calculate energy/power density trade-offs in PCM composites. Derive upper/lower bounds of conductive heat transfer in PCM composites. Effect of volume fraction, orientation, lengthscales analyzed. Conductor/PCM exhibit 5× increase in heat-flux over pure Cu (at constant temp B.C.) Insulator/PCM composites exhibit 10× increase in characteristic response time. Abstract: Thermal energy storage materials for transient thermal management applications must exhibit large energy storage densities as well as large cooling/heating power densities. The latter property has proven difficult to quantify on a materials basis because it depends on extrinsic effects. Here, we apply a previously defined cooling power figure of merit, a measure of a material's intrinsic capacity to absorb a transient heat pulse, to analyze composite phase change material heatsinks and insulants. The results demonstrate important limits on the effects of high- and low-conductivity component volume fractions, orientations, and the critical lengthscales of individual components. Champion composites are predicted to have up to 5 times greater figure of merit than pure high-conductivity materials and up to 30 times greater figure of merit than pure phase change materials. Furthermore, composites consisting of insulating materials containing dispersed phase change materials are predicted to exhibit an order of magnitude increase in their characteristic response time. These results demonstrate the utility of the cooling power figure of merit to design compact high power and energy density heatsink and insulant materials.